CRITERIA OF THE CULTIVAR MODEL AND INTERRELATIONS AMONG ECONOMICALLY USEFUL CHARACTERISTICS OF CHAENOMELES IN CONNECTION WITH BREEDING - L. D. Komar-Tyomnaya (Труды по прикладной ботанике, генетике и селекции)
Background. Chaenomeles Lindl. is a popular ornamental and relatively young fruit crop. Genetic diversity of the genus favors breeding not only in these two areas, but also aiming at the development of cultivars of a universal type. To improve the efficiency of the breeding process, a cultivar model with the maximum combination of useful qualities in one genotype is vitally needed. The goal of this work was to identify the criteria for the model of a universal Chaenomeles cultivar, select cultivars that come closest to the model in their main economic traits, and find relationships among such characteristics.Materials and methods. The study engaged 21 Chaenomeles cultivars and forms selected for their valuable qualities from the Nikita Botanical Gardens collection. They were compared with the cultivar model using cluster analysis, while correlation analysis was employed to assess interrelations between traits.Results and conclusion. Criteria were identified for the universal cultivar model of Chaenomeles (ornamental and fruit purposes) according to 27 characteristics. Seven genotypes turned out to be closest to the universal model in a set of traits (4.44 units of the Euclidean distance): PХ4/9 (4.25 units), ‘Samurai’ (4.15 units), ‘Araks’ (4.01 units), ‘Afrikanych’, ‘Shatenka’ (3.9 units), ‘Krasavitsa Madlen’ and ‘Rosemary’ (3.7 units). Different degrees of correlation between the main 17 characteristics were observed. The strongest relationships was found between the beginning of flowering and its duration (r = –0.9), between the beginning of flowering and the duration of the dormancy period (r = 0.91), between the durations of flowering and dormancy periods (r = –0.82), between the corolla diameter, the flower’s originality (r = 0.83) and the overall ornamentality of the bush (r = 0.86). A tendency to dependence was observed in 12 pairs of traits (r = 0.46 to 0.61).